1998
DOI: 10.1093/rheumatology/37.7.750
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and causes of death of 344 Danish patients with systemic sclerosis (scleroderma)

Abstract: We found a significantly increased mortality in patients with SSc, particularly in the subset of patients with diffuse skin sclerosis and in young patients. The excess mortality was due to an increase in both the SSc-related mortality and the unrelated mortality. However, all other subsets also had a significantly increased risk of death, mainly due to an increased risk of death due to causes unrelated to SSc, cancer among others. The fact that the unrelated mortality in SSc was found to be 2-fold increased su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
79
4
7

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 1 publication
11
79
4
7
Order By: Relevance
“…[10] A Danish study by Jacobsen et al reported malignancy as the primary cause of death in 19% of scleroderma patients, where cancers of the lung (43%), haematological system (13%) and breast (10%) were predominantly implicated. [13] After excluding lung malignancies which were not observed in our study, these observations relate to the most frequently affected sites of malignancy as observed within our scleroderma cohort.…”
Section: Discussionmentioning
confidence: 45%
“…[10] A Danish study by Jacobsen et al reported malignancy as the primary cause of death in 19% of scleroderma patients, where cancers of the lung (43%), haematological system (13%) and breast (10%) were predominantly implicated. [13] After excluding lung malignancies which were not observed in our study, these observations relate to the most frequently affected sites of malignancy as observed within our scleroderma cohort.…”
Section: Discussionmentioning
confidence: 45%
“…There are 2 subtypes of SSc, i.e., diffuse cutaneous SSc (dcSSc) and limited cutaneous SSc (lcSSc), according to the extent of cutaneous involvement (2); dcSSc has more extensive skin involvement, including the trunk or proximal extremities, and is associated with more internal organ involvement such as significant interstitial lung disease (ILD), cardiomyopathy, and scleroderma renal crisis (SRC) and with increased mortality (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Other rheumatic connective tissue diseases such as RA (5), SLE (6), and scleroderma (7) have been shown to be associated with increased mortality, especially with cardiovascular death. Only a few studies have investigated mortality in SS, a disease that is similar to SLE in some characteristics such as autoantibody production, but different in other respects such as the frequency of severe organ involvement (infrequent in SS).…”
mentioning
confidence: 99%